Small worlds adopted sons, pet piranhas, and other mortal concerns - Klose, Robert (University of Missouri Press, 2006)
"Collected essays by Robert Klose, longtime contributing essayist for the Christian Science Monitor. In a style comparable to that of Garrison Keillor and Jean Shepherd, Klose shares his experiences raising adoptive sons, stories of traveling abroad, memories of his childhood, and depictions of life in his small Maine community"--Provided by publisher.